Title: Can devaluation be effective in improving the balance of payments in Vietnam - Nguyen, Ngoc Thanh (ĐHKT, 2016)
Economists and policy makers in Vietnam have been discussing about the possibility of using devaluation to encourage exports and improve the balance of payments, while maintaining macroeconomic stability. The empirical results of this paper show that there has been two-way causality between money supply growth and inflation, exchange rate and inflation, and money supply growth and exchange rate in Vietnam in the 1990s. Both the long run and short run results of this paper suggest that devaluation can be implemented to encourage exports and to improve current account balance and BOP, and also to reduce the real exchange rate appreciation in the short run.